Edukasi Bahaya Minuman Berpemanis dalam Kemasan (MBDK) di SMA Santo Kristoforus II - Putriana Rachmawati; Caecilia Divany Hanan; Fionna Nathaniel; Kenneth Faustin; Jessica Manuain; Linda Sanjaya; Tommy Nugroho Tanumihardja (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
The consumption of sugar-sweetened beverages (SSBs) has increased among adolescents, leading to adverse health effects such as a higher risk of type II diabetes mellitus, cardiovascular disorders, and obesity. This educational program aims to enhance students' understanding of the adverse effects of SSB consumption through lectures and workshops. The education was conducted at SMA Santo Kristoforus II on 26 April 2024 as part of a community service activity by the Pharmacy Study Program of the Faculty of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia. The methods employed included delivering material on daily sugar requirements, the sugar metabolism cycle, the adverse effects of excessive sugar consumption, the sugar content in foods and drinks, and strategies to reduce sugar intake. Additionally, sugar content measurements were conducted on various packaged beverages using a refractometer. Pretest and post-test were used as indicators of the performance of the education process. Pretest results showed an average student understanding score of 63.8, which increased to 79.78 on the post-test, indicating a significant improvement in students' comprehension. The distribution of scores also improved, with more students achieving higher scores after their education. A satisfaction survey revealed that over 75% of students found the program beneficial and aligned with their needs. The increases in understanding and high satisfaction levels demonstrate the effectiveness of this program in conveying relevant and practical information. This educational program can be expanded to other schools to reduce SSB consumption among adolescents and mitigate health risks associated with excessive sugar intake.